Development of Anecdote Text Module Based on Interactive Multimedia in State of Vocational High School 1 Batang Toru - Riska Damayanti; M. Oky Fardian Gafari; Syahnan Daulay (BIRCU, 2019)
This study aims is to determine the results of the development of interactive multimedia-based anecdotal text learning modules by students State of Vocational High School 1 of Batang Toru. The module developed is in the form of a digital module. This type of research is development research based on the 4-D development model. With the subject of the trial consisting of design experts, material experts, Indonesian language teachers, and class X students of State of Vocational High School 1 Batang Toru. The results showed that (1) the validation of the material experts included the content eligibility is 88.0% in the good category, the feasibility of presenting is 93.7% learning module Very good category, Interactive Mutimedia aspects is 95.8% very good category, language assessment aspects 92, 5% category is very good, and aspects of project based learning is 83.3% Good category (2) validation of design experts includes initial design is 89.2% with good category, content design is 83.9% good category, digital module typography is 83.3 category good, and 87.5% illustration in good category. (3) limited trials obtained a score is 82.79% with good criteria. (4) Expanded trials obtained a score is 80.04% in the good category. The difference obtained was 13 from before and after using a digital module. This research has implications, namely the module developed will contribute to the practice , especially in the implementation of the learning process for teachers as additional teaching materials to provide convenience to the material being taught can be independent or classical.